Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 3 - Exponents, Polynomials and Functions - 3.3 Composing Functions - 3.3 Exercises - Page 256: 2


$\text{a) } f(g(x))=35x+9 \\\text{b) } g(f(x))=30x-33$

Work Step by Step

$\bf{\text{Solution Outline:}}$ With \begin{array}{l}\require{cancel} f(x)= 5x-6 \\g(x)= 7x+3 ,\end{array} to find $ f(g(x)) ,$ replace $x$ with $g(x)$ in $f.$ To find $g(f(x)),$ replace $x$ with $f(x)$ in $g.$ $\bf{\text{Solution Details:}}$ Replacing $x$ with $g(x)$ in $f$, then \begin{array}{l}\require{cancel} f(g(x))=f(7x+3) \\\\ f(g(x))=5(7x+3)-6 \\\\ f(g(x))=35x+15-6 \\\\ f(g(x))=35x+9 .\end{array} Replacing $x$ with $f(x)$ in $g$, then \begin{array}{l}\require{cancel} g(f(x))=g(5x-6) \\\\ g(f(x))=6(5x-6)+3 \\\\ g(f(x))=30x-36+3 \\\\ g(f(x))=30x-33 .\end{array} Hence, \begin{array}{l}\require{cancel} \text{a) } f(g(x))=35x+9 \\\text{b) } g(f(x))=30x-33 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.